In vitro Susceptibility and Evaluation of Techniques for Understanding the Mode of Action of a Promising Non-antibiotic Citrus Fruit Extract Against Several Pathogens - de Nova, Pedro J. G.; Carvajal, Ana; Prieto, Miguel; Rubio, Pedro (Frontiers in Microbiology, 2019)
The screening for alternatives to antibiotics is an urgent need for the pharmaceutical industry. One of these alternatives seems to be the citrus fruit extracts, which are showing a significant antibacterial activity against Gram-negative and Gram-positive bacteria. One of these citrus extracts, named BIOCITRO®, is assessed in this study to elucidate its bacteriostatic and bactericidal effect and its mode of action on the important pathogens Campylobacter coli, C. jejuni, Escherichia coli, Salmonella enterica ssp. enterica, Clostridium difficile, C. perfringens and Staphylococcus aureus. For most of the strains tested of these bacteria the product was bactericidal as well as bacteriostatic at the same concentration, and the minimum bactericidal concentrations ranged from 16 to 256 µg/mL. Regarding the mode of action, important changes in the permeability, structure, composition and morphology of the bacterial envelope were evidenced using flow cytometry, Fourier transform infrared spectroscopy and scanning electron microscopy. The main effect of the product was found over carbohydrates and polysaccharides, inducing the release of microvesicles by the cells in addition to other specific effects. During the study, the techniques used were evaluated to clarify their contribution to the knowledge of the mode of action of the product. The survival test elucidated whether the modifications displayed using other techniques affected the viability of the cells or on the contrary, the cells remained viable even with evident changes in their structure, composition or morphology. Flow cytometry showed that for some strains the proportion of cells detected with altered membrane permeability were higher than the number of nonviable cells, and therefore the damage did not affect the viability of some cells. On the contrary, some cells observed using scanning electron microscopy with no apparent damage, were demonstrated nonviable using the survival test, making this technique indispensable in studies of the mode of action of antimicrobials to make a correct interpretation of the data from other techniques.